An osteoporosis course as a separate component of problem-based learning - Iva Hoffmanová; Valér Džupa; Petr Waldauf; Robert Grill; Václav Báča (PLoS ONE, 2025)
The objective was to compare the extent of acquired knowledge regarding osteoporosis-related issues in a group of medical students who successfully completed an optional “Elective Osteoporosis Course” based on problem-based learning, and a group of medical students who completed only the mandatory curriculum. Study groups and methods Study group I was comprised of 25 fourth-year students who successfully completed the Elective Osteoporosis Course I (focused on pathophysiology, diagnostics, and pharmacological treatment), while control group I was comprised of 25 fifth-year students who successfully completed only all required fourth- and fifth-year courses, but did not participate in the elective Osteoporosis I course. Study group II was comprised of 27 fourth-year students who successfully completed the Elective Osteoporosis Course II (focused on treatment of osteoporotic fractures), while control group II was comprised of 24 sixth-year students who were preparing for final exams in surgical disciplines, but did not participate in the Elective Osteoporosis Course II. The groups were compared using a linear regression model with robust estimation of standard errors using Stata 13.1. A p-value < 0.05 was considered statistically significant. Results Study Group I scored, on average, 6.7 points higher than Control Group I on the multiple-choice test (scale –16 to +21). Study Group II scored, on average, 3.5 points higher than Control Group II on the multiple-choice test (scale –21 to +28). Both differences were statistically significant (p < 0.001, R 2 = 0.64, 95% CI: 5.2–8.1; p = 0.006, R 2 = 0.15, 95% CI: 1.1–5.9; respectively). Conclusion Results demonstrated a greater understanding in students who participated in problem-based learning medical studies relative to those who completed only the mandatory curriculum.